2020
DOI: 10.3389/fvets.2020.602984
|View full text |Cite
|
Sign up to set email alerts
|

Reference Ranges for Hematological and Biochemical Profile of Martina Franca Donkeys

Abstract: The Martina Franca donkey (MFd) is one of the largest Italian donkey breeds, considered as endangered breed. To support the conservation strategies, knowledge about the physiologic hematological parameters of MFds is needed. The aims of the study were to determine reference value for hematological and major serum parameters in a population of healthy MFds and to estimate the influence of age on these parameters. Eighty-one clinically healthy MFds (17 males and 64 females) in different ages were enrolled: group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 31 publications
12
13
1
Order By: Relevance
“…Unfortunately, we cannot answer whether or not cortisol regulated basophils number in pregnant jennies only because, to the authors’ knowledge, nobody has examined this correlation in pregnant females of other species. Levels of cholesterol and triglycerides are within the values reported by other authors [ 26 , 45 , 46 , 47 ]. Levels of cholesterol were significantly higher in juvenile animals compared to in adults, and a similar finding has been reported by other authors [ 45 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Unfortunately, we cannot answer whether or not cortisol regulated basophils number in pregnant jennies only because, to the authors’ knowledge, nobody has examined this correlation in pregnant females of other species. Levels of cholesterol and triglycerides are within the values reported by other authors [ 26 , 45 , 46 , 47 ]. Levels of cholesterol were significantly higher in juvenile animals compared to in adults, and a similar finding has been reported by other authors [ 45 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…Levels of cholesterol and triglycerides are within the values reported by other authors [ 26 , 45 , 46 , 47 ]. Levels of cholesterol were significantly higher in juvenile animals compared to in adults, and a similar finding has been reported by other authors [ 45 , 47 ]. Triglyceride levels were significantly lower in the young compared to adults.…”
Section: Discussionsupporting
confidence: 88%
“…BUN serum values were quite similar to the mean value reported for adult donkeys (16 mg/dL) [ 23 ], and to the average levels found in Martina Franca jennies in late pregnancy (18–20 mg/dL) [ 24 ], while higher mean values were observed in Ragusana jennies (27 mg/dL) [ 29 ]. In agreement with other studies on donkeys [ 24 ] and on several horse breeds [ 30 ], in our study there were no significant changes in either TP or BUN in pregnant compared to maintenance donkeys (Diet 1).…”
Section: Resultssupporting
confidence: 80%
“…In our study, the two groups of animals (maintenance and pregnancy, Diet 1) did not show significant differences in blood glucose levels. Blood glucose was slightly lower than the average glucose found in the Martina Franca breed and in the Brazilian donkey (58–59 mg/dL) [ 22 , 23 ]. The greatest differences compared to the literature were observed for the group of pregnant jennies which had lower glucose values than those reported in pregnancy for Martina Franca (ranging between 73 and 78 mg/dL) [ 24 ] and Amiata donkeys (ranging between 78 and 91 mg/dL) [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that the results obtained as a result of the hematological examination carried out to evaluate the health status of horses and donkeys are in accordance with the reference values speci ed for both species (Aiello and Moses 2016;Trimboli et al 2020).…”
Section: Discussionsupporting
confidence: 71%